The influence of reading interest on student’s argumentation ability - Wardani, Dyah Eka; Sabilla, Natasya Sal; Soleha, Nikmatu; Mustika, Rifqi Anjar; Utama, Yuda Bekti; Primatama, Yudi; Aristiawan, Aristiawan (Research in Education and Technology (REGY), 2024)
Interest in reading is closely related to argumentation skills and broader knowledge. Lack of interest in reading directly impacts students in expressing ideas and opinions to convince others. This research aimed to determine the correlation between reading interest and the argumentation ability of junior high school students. The method used quantitative with a simple linear regression analysis. The research sample was all students in class VIII of SMP Negeri 2 Wungu Madiun for the 2023 - 2024 academic year totaling 135 students. The instruments used a reading interest questionnaire and an argumentation ability test instrument. Reading interest and argumentation ability had a positive correlation with the weak category and contributed 7.1% and the remaining 92.9% was influenced by other variables not listed in this research. This proves that the higher the student’s interest in reading, the better the argumentation skill.